Flexible Organic/Inorganic Hybrid Near‐Infrared Photoplethysmogram Sensor for Cardiovascular Monitoring - Xu, Huihua; Liu, Jing; Zhang, Jie; Zhou, Guodong; Luo, Ningqi; Zhao, Ni (Advanced materials (Weinheim), 2017)
Wearable photoplethysmogram (PPG) sensors offer convenient and informative measurements for evaluating daily physiological states of individuals. In this work, epidermal and flexible near‐infrared (NIR) PPG sensors integrating a low‐power, high‐sensitivity organic phototransistor (OPT) with a high‐efficiency inorganic light‐emitting diode are developed. By exploiting an organic bulk heterojunction active layer and a bilayer gate dielectric design, a low voltage (<3 V) operated OPT with NIR responsivity as high as 3.5 × 105 A W−1 and noise equivalent power of 1.2 × 10−15 W Hz−1/2 is achieved, greatly surpassing commercial available silicon‐based photodetectors. In addition, the ultrathin encapsulation structure renders the device highly flexible and allows transfer printing of the device directly onto human skin. It is demonstrated that the epidermal/flexible PPG sensors are capable of continuously monitoring heart rate variability and precisely tracking the changes of pulse pressure at different postures of human subjects with the aid of electrocardiogram monitoring, exhibiting more reliable performance than commercial PPG sensors while consuming less power. The study suggests that the hybrid PPG sensor design may provide a promising solution for low‐power, real‐time physiological monitoring. Epidermal and flexible photoplethysmogram (PPG) sensors that can be operated in the near‐infrared regime with high sensitivity are demonstrated. The sensors are capable of continuously monitoring heart rate variability and precisely tracking the changes of pulse pressure at different postures of subjects with the aid of electrocardiogram monitoring, exhibiting more reliable performance than conventional PPG sensors while consuming less power.